2021
DOI: 10.1186/s12885-021-08651-5
|View full text |Cite
|
Sign up to set email alerts
|

Sniffer dogs can identify lung cancer patients from breath and urine samples

Abstract: Background Lung cancer is the most common oncological cause of death in the Western world. Early diagnosis is critical for successful treatment. However, no effective screening methods exist. A promising approach could be the use of volatile organic compounds as diagnostic biomarkers. To date there are several studies, in which dogs were trained to discriminate cancer samples from controls. In this study we evaluated the abilities of specifically trained dogs to distinguish samples derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…It is associated with the cancer smell, the end-product of metabolic changes producing patterns of volatile organic compounds (VOCs) observed in cancers [ 34 , 35 , 36 ]. Dogs trained with olfactory associative learning are known to recognize specific smells in urine for detecting human lung and breast cancer [ 37 , 38 , 39 , 40 ]. Specifically for breast cancer, the study by Woollam et al identified six VOCs in mice via gas chromatography-mass spectrometry QTOF that could potentially be the basis of screening test with suitable separation of cancer/non-cancer with ROC AUC of 0.96 [ 41 ].…”
Section: Non-invasive Early Cancer Detection Using Body Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with the cancer smell, the end-product of metabolic changes producing patterns of volatile organic compounds (VOCs) observed in cancers [ 34 , 35 , 36 ]. Dogs trained with olfactory associative learning are known to recognize specific smells in urine for detecting human lung and breast cancer [ 37 , 38 , 39 , 40 ]. Specifically for breast cancer, the study by Woollam et al identified six VOCs in mice via gas chromatography-mass spectrometry QTOF that could potentially be the basis of screening test with suitable separation of cancer/non-cancer with ROC AUC of 0.96 [ 41 ].…”
Section: Non-invasive Early Cancer Detection Using Body Fluidsmentioning
confidence: 99%
“…A test based on a urine sample may be a suitable alternative, as metabolome signatures and specific VOCs have been identified in the urine for colorectal cancer [ 42 ]. Many recent studies have highlighted the application of urinary volatile organic compounds found in urine for cancer type discrimination, such as prostate, renal, breast, and lung, among others [ 39 , 43 , 44 , 45 ].…”
Section: Non-invasive Early Cancer Detection Using Body Fluidsmentioning
confidence: 99%
“…Obesity--and its associated comorbidities--has also been linked to diet and levels of activity in humans, cats, dogs, and other species (26)(27)(28). In some cases, the human-animal bond can be leveraged to motivate lifestyle behavioral changes with positive health effects (29).…”
Section: Ncds Environments and Threatsmentioning
confidence: 99%
“…VOCs are a type of organic matter that exists in the form of steam at room temperature, which can be divided into aromatic hydrocarbons, alkanes, olefins, halohydrocarbons, esters, and ketones. Due to their distinct odors, VOCs emitted from different substrates can be detected by gas chromatography-mass spectrometry (GC-MS), gas chromatography-ion mobility spectrometry (GC-IMS), electronic nose (E-Nose), or even trained sniffer dogs ( 10 12 ). Bhatt et al.…”
Section: Introductionmentioning
confidence: 99%